Structures of ISCth4 transpososomes reveal the role of asymmetry in copy‐out/paste‐in DNA transposition. (2nd October 2020) - Kosek, Dalibor; Hickman, Alison B; Ghirlando, Rodolfo; He, Susu; Dyda, Fred
Abstract: Copy‐out/paste‐in transposition is a major bacterial DNA mobility pathway. It contributes significantly to the emergence of antibiotic resistance, often by upregulating expression of downstream genes upon integration. Unlike other transposition pathways, it requires both asymmetric and symmetric strand transfer steps. Here, we report the first structural study of a copy‐out/paste‐in transposase and demonstrate its ability to catalyze all pathway steps in vitro . X‐ray structures of IS C th4 transposase, a member of the IS 256 family of insertion sequences, bound to DNA substrates corresponding to three sequential steps in the reaction reveal an unusual asymmetric dimeric transpososome. During transposition, an array of N‐terminal domains binds a single transposon end while the catalytic domain moves to accommodate the varying substrates. These conformational changes control the path of DNA flanking the transposon end and the generation of DNA‐binding sites. Our results explain the asymmetric outcome of the initial strand transfer and show how DNA binding is modulated by the asymmetric transposase to allow the capture of a second transposon end and to integrate a circular intermediate. Synopsis: Bacterial DNA mobility via "copy‐out/paste‐in" transposition, a major contributor to the emergence of antibiotic resistance, requires both asymmetric and symmetric strand transfer steps. Three IS C th4 transposase structures with DNA substrates along the pathway provide first insight into the underlying transpososome architecture and molecular reaction mechanisms. IS C th4 transposase catalyzes all reactions necessary for copy‐out/paste‐in transposition in vitro . An asymmetric dimer of IS C th4 transposase binds to a single terminal inverted repeat through an array of N‐terminal domains in a bi‐partite manner. Conformational changes in catalytic domains control the path of flanking DNA and the sequential generation of additional DNA binding sites. Abstract : Structures of IS C th4 transposase/DNA complexes at different stages of the transposition pathway provide first insight into transpososome architecture and reaction mechanism of this major bacterial DNA mobility pathway.